AdvancED Game Design with Flash - van der Spuy, Rex (Apress : Imprint: Apress, 2010)
Creating games in Flash is a never-ending journey of exploration, learning, and most of all, fun. Once you've mastered the basics, a new world is opened up to you, enabling you to take your existing skills to the next level and discover new skills that will in turn open new doors. This book is a direct continuation of Foundation Game Design with Flash, and is a complete point-by-point roundup of the most important skills a Flash game designer needs to know. You'll increase your ActionScript knowledge and your game design skills while creating some excellent example games. You'll learn advanced collision detection skills; professional AI and pathfinding; and how to load and save game data, create destructible environments, and build and switch game levels.  Each chapter highlights a new advanced technique illustrated by practical examples. Examples of games are given in a variety of genres, all of which take an object-oriented programming approach. Advanced game design topics are covered, including vector-based collision reaction, pathfinding, billiard ball physics, and modeling game data.